We have to solve the equation |6t - 9| - 21 =0

|6t - 9| - 21 =0

=> |6t - 9| = 21

This gives us two equations

6t - 9 = 21

=> 6t = 21 + 9

=> 6t = 30

=> t = 30/6

=> t...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve the equation |6t - 9| - 21 =0

|6t - 9| - 21 =0

=> |6t - 9| = 21

This gives us two equations

6t - 9 = 21

=> 6t = 21 + 9

=> 6t = 30

=> t = 30/6

=> t = 5

And 9 - 6t = 21

=> -6t = 21 - 9

=> -6t = 12

=> t = 12/-6

=> t = -2

**Therefore we have t = -2 and t = 5**